The cunning of rights : law, life, biocultures - Chandra, Rajshree (New Delhi : Oxford University Press, 2016)
This work analyses the theoretical and philosophical frames of new (biotic) property, and assesses how its altered metaphysics inscribes itself in the politics of genetic resources. It probes how rights get framed within and by law and attempts to uncover the cunning or duplicitous nature of these rightsthe chasm between their intended benefits and their actual outcomes.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 5, 2016).
Keywords: Biotechnology -- Law and legislation; Right of property; Law; Laws of specific jurisdictions & specific areas of law